Mindfulness-Based Cognitive Therapy for Mental Health Professionals - a Pilot Study - Ruths, F; de Zoysa, N; Frearson, S; Hutton, J; Williams, J; Walsh, J (2013)
We investigated the adherence of mental health professionals to a Mindfulness-Based Cognitive Therapy (MBCT) programme as well as the impact of MBCT on mindful awareness and attention, psychological well-being and distress, state and trait anxiety, worry and satisfaction with life. The design comprised of a prospective uncontrolled intervention study with pre- and post-measurements of meditation adherence and measures of psychological well-being. Twenty-seven mental health professionals participated in an 8-week MBCT programme for relapse prevention of depression, modified for healthy individuals. Their homework, mindful awareness and attention (Mindful Awareness and Attention Scale), general psychological well-being (General Health Questionnaire), state and trait anxiety (State-Trait Anxiety Inventory), satisfaction with life (Satisfaction with Life Scale), general psychopathology (Brief Symptom Inventory) as well as worry (Penn State Worry Questionnaire) were measured at week 1 and 8 during the intervention and at week 20 as follow-up. Twenty four of 27 (88 %) mental health professionals completed the course and were included in the analysis. Of these, 75 % (18 of 24) were female with a mean age of 36 years and a mean experience in cognitive behavioural therapy (CBT) of 6 years. Sixty-three per cent (15 of 24) reported continued practice at 20-week follow-up. A statistically significant improvement of mindful awareness and psychological well-being, with significant reduction in worry, trait anxiety and general psychopathology, was observed in participants who continued some form of meditation practice during the follow-up period. The majority of mental health professionals adhered to the MBCT meditation practice, and the more they practised mindfulness meditation, the more they experienced an increase in mindful awareness and attention, general psychological well-being and a decrease in general psychopathology, trait anxiety and worry. © 2012 Springer Science+Business Media, LLC.